Effects of elk browsing and water table on willow growth and physiology: implications for willow restoration in Yellowstone National Park - Bilyeu, Danielle, author; Hobbs, N. Thompson, advisor; Cooper, David J., committee member; Detling, James K., committee member; Knapp, Alan K., committee member (Colorado State University. Libraries, 2006)
Restoration of degraded ecosystems often requires addressing both the direct and indirect effects of stressors. The removal of wolves from the northern range of Yellowstone National Park, USA, has allowed abundant elk populations to heavily browse riparian woody plant communities, resulting in reduced willow stature, extent, and reproduction. Following the reintroduction of wolves, elk browsing on riparian willow has lessened, but willow recovery may be limited due to indirect effects. During wolf absence, elk use of riparian willows competitively excluded beaver, and although beaver are present and active in adjacent areas, they have not reestablished dams on many formerly occupied streams in the northern range. Decades of beaver absence has resulted in stream channel incision and lower water tables near these streams. Because water availability limits willow growth, I hypothesize that a feedback between low water table, low willow productivity, and beaver absence may limit willow recovery even in the absence of elk browsing. I conducted a factorial experiment to examine the response of willow to the cessation of browsing under hydrologic conditions representing the presence vs. absence of beaver. Factors in the experiment included exclosures and dams. Productivity and rapid height gain in browse-protected plants depended on water table treatment. After four years of protection from elk browsing, Salix geyeriana with ambient water table gained only 60 cm in height, and had lower productivity, photosynthetic rate, stomatal conductance, and water potential than plants in control plots. In contrast, browse-protected willows with elevated water table gained 110 cm in height, and had similar productivity to control plants. Elevated water table also increased height gain and productivity in browsed plots. Using a new technique to detect small changes in browsing pressure, I observed that water table elevation doubled the height gain of willows in response to a slight decrease in ambient browsing pressure occurring over the course of the experiment. Because lower water availability limits willow height and productivity, and browsing appears to improve water relations, removing browsing under conditions of low water availability is unlikely to result in tall, productive willow stands. In areas where beaver absence has altered historic hydrologic conditions, reducing elk browsing may not be sufficient for willow recovery. This research underscores the need for assessing indirect effects of ecosystem stressors to inform restoration efforts.
Keywords: ecology; botany; environmental science